Paper making and characterization from waste coconut and tofu dregs - Erdiana Gultom; Hestina Hestina; Nova Florentina; Barita Aritonang (Jurnal Pendidikan Kimia (JPKim), 2021)
Research on paper made from coconut and tofu waste has been carried out using the alkalization method of separation technique, with the optimum composition as follows: NaOH concentration used is 3.0% and cooking temperature is 100 0C and the time required is 90 minutes. The results of the catheterization test of paper made from coconut dregs and tofu have a water content of 3.2%; pH 6.9, pulp content 65.75%; cellulose content 80.22%; lignin content 18.27%. The results of the FT-IR spectrum analysis of coconut pulp and tofu pulp are suitable for use as raw materials for making paper because they contain cellulose fibers. This is indicated by the appearance of the O-H hydroxyl group which is observed at a wavenumber of 3312 cm-1. Based on the SEM results, the surface morphology of the coconut pulp and tofu combination paper shows that the surface structure is the denser the fiber bonds, the smaller the fiber diameter, the better the mechanical properties. The results of the research conclusions explain that, paper made from coconut and tofu waste has met the requirements set by SNI 14-0444-1989.Keywords: Paper, Cellulose, Coconut pulp, Tofu pulp, Lignin